UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS DAN RPP MELALUI SUPERVISI AKADEMIK YANG BERKELANJUTAN DI SDN 09 KOTO PULAI KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Emi, Emi (STKIP Pesisir Selatan, 2018)
Each process must always include three main activities: planning, implementation and evaluation. Similarly, what happens with the teaching and learning process at school. A teacher is required to plan, implement and evaluate learning. The learning planning process that must be carried out by a teacher includes the main activities are 1) Making an annual program 2) Making a syllabus 3) Making a semester program 4) Making a learning plan 5) And making a repeat program /evaluation. Of the five elements mentioned above, the syllabus and RPP are the minimum preparation for a teacher when they want to teach. Based on the results of the analysis in the 2017/2018 school year at SDN 09 Koto Pulai, there were problems with the low number of teachers making lesson plans especially the preparation of syllabus and RPP. To examine the weak performance of teachers in this regard, a study was conducted to see the extent to which the principal's academic supervision step could improve teacher competency in the preparation of the syllabus and the Learning Implementation Plan.